An optimized fluorogenic ADAMTS13 assay with increased sensitivity for the investigation of patients with thrombotic thrombocytopenic purpura - Muia, J.; Gao, W.; Haberichter, S. L.; Dolatshahi, L.; Zhu, J.; Westfield, L. A.; Covill, S. C.; Friedman, K. D.; Sadler, J. E. (Journal of thrombosis and haemostasis, 2013)
Summary Background Most ADAMTS13 assays use non‐physiological conditions (low ionic strength, low pH, barium chloride), are subject to interference from plasma proteins, hemoglobin and bilirubin, and have limited sensitivity, especially for inhibitors. Objectives We addressed these constraints by designing a substrate that can be used in undiluted plasma. Methods A polypeptide was expressed in E. coli that corresponds to von Willebrand factor Gln1599‐Arg1668, with mutations N1610C and K1617R and an N‐terminal Gly. Substrate FRETS‐rVWF71 was prepared by modifying Cys1610 with DyLight 633 (abs 638 nm, em 658 nm) and the N‐terminus with IRDye QC‐1 (abs 500–800 nm). Assays were performed at pH 7.4 in 150 mm NaCl, 10 mm CaCl2. Results Serum and plasma anticoagulated with citrate or heparin had equivalent ADAMTS13 activity with FRETS‐rVWF71. Neither bilirubin (≤ 20 mg dL−1) nor hemoglobin (≤ 20 g L−1) interfered with product detection. Assays with FRETS‐rVWF71 and FRETS‐VWF73 gave similar results (R2 = 0.95) for plasma from 80 subjects with thrombotic microangiopathy, 22 subjects with other causes of thrombocytopenia, and 20 healthy controls. The limit of detection with FRETS‐rVWF71 for ADAMTS13 activity was ≤ 0.3%. Inhibitor assays with FRETS‐rVWF71 gave titers ~2.5‐fold higher than with FRETS‐VWF73 and clearly distinguished patients with and without inhibitors. Conclusions FRETS‐rVWF71 is suitable for ADAMTS13 assays in minimally diluted plasma or serum without interference from proteins, bilirubin or free hemoglobin in plasma. Optimized detection of ADAMTS13 inhibitors will facilitate the monitoring of antibody responses during the treatment of thrombotic thrombocytopenic purpura.